2015
DOI: 10.1177/0961203315596079
|View full text |Cite
|
Sign up to set email alerts
|

Who receives contraception counseling when starting new lupus medications? The potential roles of race, ethnicity, disease activity, and quality of communication

Abstract: Objective Family planning discussions are an important aspect of medical care for women with systemic lupus erythematosus (SLE) as active disease is a risk factory for poor pregnancy outcomes, and the medications used for treatment can be harmful to the fetus when used during conception and pregnancy. Our objective was to examine the impact of patient perception of quality and type of communication on receiving contraception counseling. Methods Data were derived from patients enrolled in the University of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…10 It is not surprising that unplanned pregnancy is so common, as 1/3 of women with lupus starting teratogenic medications are given no instructions to avoid conception. 11 The European League Against Rheumatism (EULAR) guidelines for lupus management in pregnancy emphasize controlling lupus through the use of compatible medications, particularly hydroxychloroquine, azathioprine, and prednisone only when needed. 9 They also recommend against the use of rheumatic teratogens.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is not surprising that unplanned pregnancy is so common, as 1/3 of women with lupus starting teratogenic medications are given no instructions to avoid conception. 11 The European League Against Rheumatism (EULAR) guidelines for lupus management in pregnancy emphasize controlling lupus through the use of compatible medications, particularly hydroxychloroquine, azathioprine, and prednisone only when needed. 9 They also recommend against the use of rheumatic teratogens.…”
Section: Discussionmentioning
confidence: 99%
“…B. Schwarz, Parisi, Williams, Shevchik, & Hess, 2012;E. B. Schwarz et al, 2007;Stancil et al, 2016;Steinkellner et al, 2010;Teichert et al, 2010;Uuskula et al, 2018;Wieck et al, 2007), while others used patients surveys (Algoblan et al, 2019;Banas et al, 2014;Bell et al, 2002;Boucher & Beaulac-Baillargeon, 2006;Brandenburg et al, 2017;Brinker et al, 2005;Castaneda et al, 2008;Chang et al, 2018;Ferguson et al, 2016;Goyal et al, 2015;Lelubre et al, 2018;Leverenz et al, 2019;Mitchell et al, 1995;Ozyurt & Kaptanoglu, 2015;Rao et al, 2000;E. B. Schwarz, Mattocks, et al, 2013;Shilalukey et al, 1997;Tsur et al, 2008;Valle et al, 1998;Werner et al, 2014;Yazdany et al, 2011), a combination of medical records and patient surveys (Bosak et al, 2019;Entezari-Maleki et al, 2012;Hogan et al, 1988;E.…”
Section: Risk Managementmentioning
confidence: 99%
“…Data sharing is not applicable to this article as no new data were created or analyzed in this study. (Bhakta et al, 2015;Brandenburg et al, 2017;Brinker et al, 2005;Castaneda et al, 2008;Cheetham et al, 2006;DiPietro Mager, Mills, & Snelling, 2018;Ferguson et al, 2016;Force et al, 2012;Fritsche et al, 2011;Gotlib et al, 2016;Goyal et al, 2015;Hayward et al, 2016;Landis et al, 2012;Leverenz et al, 2019;Mitchell et al, 1995;Mody, Farala, et al, 2015;Pinheiro et al, 2013;Rao et al, 2000;E. B. Schwarz et al, 2010;E.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nearly half of reproductive‐age women with SLE in another survey reported having had unprotected sex, with 23% of respondents having had unprotected sex most of the time, in the prior 3 months . Another survey reported that 33% of women with SLE did not receive contraceptive counseling when starting new medications, and individuals with the highest disease activity were least likely of all patients to receive contraceptive counseling . A study by Chakravarty et al reported that a majority of European and US women with SLE, RA, and inflammatory bowel diseases (IBD) felt that family planning concerns were inadequately addressed by their providers.…”
Section: Inadequacies Of Family Planning Counselingmentioning
confidence: 99%